Zoned out: how zoning commonly excludes the missing middle - Snawerdt, Alison Nicole (My University, 2025)
The lack of affordable housing in Kansas is exacerbated by restrictive zoning codes, high prices, suburban sprawl, and a housing market that prioritizes single-family developments over diverse, higher-density alternatives. With increasing demand for walkable, sustainable neighborhoods, innovative housing solutions are needed to address these challenges. This study examines the feasibility of “missing middle” housing— duplexes, townhomes, cottage courts, and other multi-unit housing types—across three Kansas cities: Kansas City Kansas, Salina, and Cottonwood Falls. The research involved zoning code analysis, missing middle analysis, and spatial mapping to identify barriers and opportunities for increasing density and affordability. A projective design approach was also employed to propose modular, prefabricated housing models that create missing middle housing types. Findings reveal that many Kansas zoning codes do not actively accommodate missing middle housing, limiting its development despite demand. Additionally, suburban sprawl has increased infrastructure costs and environmental impacts while failing to provide affordable, community-oriented living spaces. The proposed design solutions demonstrate how innovative planning strategies can assist in bridging this gap, promoting affordability and walkability. While limitations in zoning accessibility and data availability remain, this research underscores the need for policy reform to create affordable housing solutions in Kansas.
Keywords: Zoning; Missing middle; Density; Affordable housing